2012
DOI: 10.1159/000337715
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Associated Risk Factors and Effects of Hypothyroidism in Pregnancy: A Study from North India

Abstract: Background and Objective: There is a controversy regarding universal versus targeted screening for hypothyroidism during pregnancy. We studied the prevalence and the associated risk factors of hypothyroidism. The secondary objective of the study was to compare the maternal and perinatal outcomes in overt and subclinical hypothyroidism. Methods: We screened 1,005 antenatal patients for hypothyroidism with a thyrotropin assay. Patients diagnosed with hypothyroidism were further tested for anti-thyroid peroxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 35 publications
3
33
1
1
Order By: Relevance
“…3 Age more than thirty years was not found to be associated with maternal hypothyroidism in the study conducted by Potlukova et al which was similar to the present study where only 20% cases belonged to that age group. 4 In a study conducted on pregnant women in Bangladesh, hypothyroidism was associated with development of gestational diabetes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…3 Age more than thirty years was not found to be associated with maternal hypothyroidism in the study conducted by Potlukova et al which was similar to the present study where only 20% cases belonged to that age group. 4 In a study conducted on pregnant women in Bangladesh, hypothyroidism was associated with development of gestational diabetes.…”
Section: Discussionsupporting
confidence: 91%
“…In the study by Sharmeen et al there was a positive association which was similar to another study by Nazarpour et al in Iran. 5,8 Increased association was also found in the study by Mannisto et al between hypothyroidism in pregnancy and preeclampsia as well by Goel et al 2,3 No association with hypertensive disorders were found by Medici et al as well as by Kumru et al 7,9 Similar results were reported in the study by Gudovic et al 6 In this study there was no increased association for the development of hypertension in the case and control groups.…”
Section: Discussionsupporting
confidence: 86%
“…[1][2][3] The adverse perinatal outcomes include low birth weight, fetal distress, increase in admission to neonatal ICU, neonatal hypothyroidism, IUGR and IUD. [1][2][3] Thyroid disorders satisfy most of the criteria for a disease to warrant population screening. 4 They are common and treatable.…”
Section: Introductionmentioning
confidence: 99%
“…12 A study done at Government Medical College and Hospital, Chandigarh, 2012 by Goel P et al showed prevalence of hypothyroidism was 6.3%. 13 Sisodia J et al gives the prevalence of hypothyroidism in pregnancy -3.7%. 13 They found that age of hypothyroid pregnant women varied from 20-35 years, with median age of 25 years.…”
mentioning
confidence: 99%
“…13 Sisodia J et al gives the prevalence of hypothyroidism in pregnancy -3.7%. 13 They found that age of hypothyroid pregnant women varied from 20-35 years, with median age of 25 years.…”
mentioning
confidence: 99%